Gender, ethnicity and identity work in the family business. (9th March 2015) - Aygören, Huriye; Nordqvist, Mattias
We study how family business members form and manage their individual identities in a family business context, attending both to individual and societal circumstances. We depart from the understanding that the institutions of family and business are media by which diverse individual and social identities are mutually enacted, formed and continuously worked out. In order to bring in a combination of important individual and societal influences and processes, we draw a framework of an identity work with a particular focus on two specific habitats of meaning: gender and ethnicity. We show that formation and management of plural identities take a distinctive form, and that the two habitats of meaning - gender and ethnicity - prove to be fundamental in organising and performing in the family business context.